The University Technology Research and Micro Enterprises - Carrión Muñoz, Rolando Víctor (2000)
This article makes some proposals to encourage technological research {Ogica college, despite the economic crisis in the country, taking advantage of the few state resources that could catch em upport of micro enterprises, which is the sector most in need of support and offers the greatest opportunities.